(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The most common sources responsible for the high level of anions in the environment are municipal and industrial wastewaters and runoff or leachate from manured or fertilized agricultural lands. This study was conducted to assess the seasonal variations of Nitrite, Nitrate, and Phosphate in soil sampled obtained from Dutsin-Ma irrigation farmlands, A total of ten (10) soil samples were collected from ten irrigation farmlands during dry and wet season. The samples were ground, sieved, and analysed using standard analytical techiniques. Descriptive and inferential statistics were adopted for data interpretations. The concentrations of nitrite, nitrate and phosphate in soil during dry season were 0.24 ± 0.02, 1.06 ± 0.07 and 5.65 ± 0.063 mg/kg respectively while levels during wet season were 1.55 ± 0.03, 2.51 ± 0.04, and 12.3 ± 0.08 mg/kg. There was significant difference in the levels of these anions across the sampling sites (P < 0.05).